“Si Tole” Chatterbot untuk Melatih Rasa Percaya Diri Menggunakan Naive Bayes Classification - Zamah Sari; Moechammad Sarosa; Suhari (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Observing the behavior and character of children today, many parents are worried about their child's development. Educational observers convey the necessity of character education from an early age to instill in them with morality and noble character. Having a strong character and quality, young generation will become an ethical, tough, and superior generation. Various efforts were made to provide character education to children. One of them is to train the level of confidence of children by inviting them to speak and express opinions in the form of text/chat. In order to help that, a chat app that can help kids to tell stories in the form of text/chat was built, so the kids accustom to expressing opinions and confidently talk to others and happy to hear it. The character education raised in this application is to increase the confidence level of the child. The topics raised as conversation on the Si Tole app are about friendship, joy (food, books, movies), recreation, birthday parties, hopes, and dreams. By practicing to talk to Si Tole Chatterbot, it is expected that children's character development will be better. This application is suitable to be a medium of character education for adolescents (Primary School/Junior High School) to improve their confidence.